2018
DOI: 10.1111/jon.12566
|View full text |Cite
|
Sign up to set email alerts
|

Brief Computer‐Based Information Processing Measures are Linked to White Matter Integrity in Pediatric‐Onset Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE Pediatric‐onset multiple sclerosis (POMS) is a demyelinating disorder with unique clinical challenges. A brief computer‐administered cognitive screening battery measuring processing speed (Cogstate) and the Brief International Cognitive Assessment in MS (BICAMS) detect cognitive impairment in POMS. The neuroanatomic correlates of these deficits are incompletely understood. The purpose of this study is to define the neuroanatomic underpinnings of deficits identified with cognitive screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
(139 reference statements)
0
7
0
Order By: Relevance
“…Findings yielded by commonly used tools were sometimes discrepant across studies. For instance, SDMT has been recommended and widely used as a screening tool in adult and pediatric MS [ 26 , 29 ], whereas its sensitivity in pediatric MS was occasionally challenged [ 17 , 21 , 30 , 31 ], particularly in early stage of the disease. Brief international cognitive assessment for multiple sclerosis (BICAMS) and a Cogstate brief battery were shown to exhibit comparable sensitivity in detecting cognitive impairment in POMS [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings yielded by commonly used tools were sometimes discrepant across studies. For instance, SDMT has been recommended and widely used as a screening tool in adult and pediatric MS [ 26 , 29 ], whereas its sensitivity in pediatric MS was occasionally challenged [ 17 , 21 , 30 , 31 ], particularly in early stage of the disease. Brief international cognitive assessment for multiple sclerosis (BICAMS) and a Cogstate brief battery were shown to exhibit comparable sensitivity in detecting cognitive impairment in POMS [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brief international cognitive assessment for multiple sclerosis (BICAMS) and a Cogstate brief battery were shown to exhibit comparable sensitivity in detecting cognitive impairment in POMS [ 19 ]. These two batteries were subsequently employed in a study investigating the neuroanatomical correlates of cognitive impairment in POMS; however, the findings cast doubt on the discriminative power of BICAMS [ 31 ]. Trail making test (TMT)-B performance more readily differentiated between POMS and controls compared to TMT-A in earlier studies [ 13 , 30 ], whereas the reverse was found in later studies [ 21 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional examination of brief batteries includes a recent study, which examined the efficacy of using a 15-min battery (Brief International Cognitive Assessment of MS: BICAMS) including measures of visual learning (brief visuospatial memory test—revised: BVMT-R), verbal learning (Rey auditory verbal learning test: RAVLT), and attention (SDMT), compared to a 15-min computer-administered battery of speeded processing tasks (Cogstate brief battery) and found similar detection rates of cognitive dysfunction across batteries [69]. Similarly, Bartlett et al (2018) compared Cogstate and BICAMS outcomes in patients with POMS and found that the Cogstate composite score revealed slowing in the POMS group compared to controls, while the BICAMS composite did not differentiate the groups [70]. Interestingly, other disease-related measures may also help in identifying/screening for cognitive impairment in patients with POMS.…”
Section: Assessment Of Cognitive Functioning In Pomsmentioning
confidence: 99%
“…There has been limited examination of DTI and cognitive functioning, but Bartlett et al (2019), using Cogstate and BICAMS, found that the Cogstate composite showed correlations with regional FA and correlated significantly with uncinated fasciculus FA. BICAMS only showed weak to moderate correlations with FA [70]. De Meo and colleagues [92] found general abnormalities in patients with POMS on DT-MRI, as well as differences in increased activation of the left thalamus, anterior insula, and anterior corpus callosum (ACC) and decreased recruitment of the right precuneus on fMRI compared to healthy controls during a continuous performance test (assessing sustained attention).…”
Section: Disease Characteristics Associated With Cognitive and Psymentioning
confidence: 99%